Social Media Account as an Object of Virtual Property - Некіт, Катерина Георгіївна; Некит, Екатерина Георгиевна; Nekit, Ekaterina G.; Некіт, К. Г.; Nekit, Kateryna H.; Nekit, Kateryna (Brno : Masaryk University, 2020)
This article analyzes the concept of virtual property as well as the legal nature of social media accounts to explore whether these can be considered objects of property, in particular, of virtual property rights. It examines the essence of virtual property and reveals the specifics of owner’s powers regarding to digital assets. It also specifies what kind of objects should be treated as digital assets. The technical and legal nature of a social media account are analyzed to reveal whether the latter can be considered as “possession” in terms of Protocol No. 1 to the Convention for the Protection of Human Rights and Fundamental Freedoms. Some legal issues regarding to the use of a social media account including the division of rights to business accounts and inheritance of social media accounts are investigated. The approaches in various countries to the problem of determination of the post-mortem fate of digital assets are analyzed, and a unified tendency to consider social media accounts as part of the estate transferred to the heir is revealed. The conclusion is drawn that the extension of the property regime to social media accounts could ensure an appropriate legal protection of users’ rights.

У цій статті аналізується концепція віртуальної власності, а також юридична природа облікових записів у соціальних мережах, щоб з’ясувати, чи можна їх вважати об’єктами власності, зокрема, прав віртуальної власності. Вивчається зміст віртуальної власності та розкриваються особливості повноважень власника щодо цифрових активів. Також визначається, який тип об'єктів слід розглядати як цифрові активи. Проаналізовано технічну та юридичну природу акаунта в соціальних мережах для виявлення, чи можна розглядати його як «володіння» з точки зору Протоколу № 1 до Конвенції про захист прав людини та основних свобод. Досліджуються деякі юридичні питання щодо використання облікового запису в соціальних мережах, включаючи розподіл прав на бізнес-рахунки та спадкування облікових записів у соціальних мережах. Проаналізовано та уніфіковано підходи різних країн до проблеми визначення визначальної долі цифрових активів, виявлено тенденцію розглядати акаунти в соціальних мережах як частину спадщини, переданої спадкоємцю. Зроблено висновок, що поширення режиму власності на облікові записи в соціальних мережах може забезпечити належний правовий захист прав користувачів.

В этой статье анализируется концепция виртуальной собственности, а также юридическая природа учетных записей в социальных сетях, чтобы выяснить, можно ли их считать объектами собственности, в частности, прав виртуальной собственности. Изучается содержание виртуальной собственности и раскрываются особенности полномочий собственника в отношении цифровых активов. Также определяется, какой тип объектов следует рассматривать как цифровые активы. Проанализировано техническую и юридическую природу аккаунта в социальных сетях для выявления, можно рассматривать его как «владение» с точки зрения Протокола № 1 к Конвенции о защите прав человека и основных свобод. Исследуются некоторые юридические вопросы использования аккаунта в социальных сетях, включая распределение прав на бизнес-счета и наследования учетных записей в социальных сетях. Проанализированы и унифицированы подходы разных стран к проблеме определения конечной судьбы цифровых активов, выявлена ​​тенденция рассматривать аккаунты в социальных сетях как часть наследства, переданного наследнику. Сделан вывод, что распространение режима собственности на учетные записи в социальных сетях может обеспечить надлежащую правовую защиту прав пользователей.
Nekit K. Social Media Account as an Object of Virtual Property / K. Nekit // Masaryk University Journal of Law and Technology. – V. 14 (2). – Brno : Masaryk University, 2020. – P. 201-226.
Keywords: Account; Digital Assets; Inheritance; Possession; Social Media; Users; Virtual Property; обліковий запис; цифрові активи; спадщина; володіння; соціальні медіа; користувачі; віртуальна власність; аккаунт; цифровые активы; наследство; владение; социальные медиа; пользователи; виртуальная собственность; Research Subject Categories::LAW/JURISPRUDENCE